2023
DOI: 10.1007/s10811-023-03133-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of a natural marine algae polysaccharide (λ-carrageenan) on seabream erythrocytes, tumour cell lines and marine bacterial pathogens

Jose Carlos Campos-Sánchez,
Francisco A. Guardiola,
María Ángeles Esteban

Abstract: Carrageenan is a high molecular weight sulphated polysaccharide used to induce experimental inflammation in mammals. In addition, it possesses a wide variety of properties that have not yet been studied in fish. This study evaluated the hemagglutinating, hemolytic, cytotoxic, and antibacterial activities of λ-carrageenan. The results showed that λ-carrageenan has hemagglutinating and hemolytic activities on gilthead seabream erythrocytes, which were dose and time-dependent during the first 6 h of incubation. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…It is also suggested that the positive charges of glycoprotein on surface of the erythrocyte membrane could be attracted by the negative charges of kappa carrageenan or their carboxymethylated derivatives, result increases the ability of erythrocytes to adhere and form agglutination (Wang et al 2021). The similar agglutination has also been recorded for carrageenan (Silva et al 2010;McKim 2014;Campos-Sánchez et al 2023). of the red alga K. striatus showed the physicochemical properties, structure and biological activities similar well to those of carboxymethyl kappa carrageenans reported, including degree and sites of carboxymethyl group substitution in kappa carrageenan structure, molecular weights, antioxidant and hemagglutination activity.…”
Section: Hemagglutination Activitymentioning
confidence: 74%
“…It is also suggested that the positive charges of glycoprotein on surface of the erythrocyte membrane could be attracted by the negative charges of kappa carrageenan or their carboxymethylated derivatives, result increases the ability of erythrocytes to adhere and form agglutination (Wang et al 2021). The similar agglutination has also been recorded for carrageenan (Silva et al 2010;McKim 2014;Campos-Sánchez et al 2023). of the red alga K. striatus showed the physicochemical properties, structure and biological activities similar well to those of carboxymethyl kappa carrageenans reported, including degree and sites of carboxymethyl group substitution in kappa carrageenan structure, molecular weights, antioxidant and hemagglutination activity.…”
Section: Hemagglutination Activitymentioning
confidence: 74%